Raw data : infographic designers' sketchbooks - Heller, Steven, 1950-; Landers, Rick, ....- (London : Thames & Hudson, 2014)
Raw Data presents work by seventy-three of the world's most innovative information graphics designers ‘A peek at cognition's wider shores … [a] splendid compilation' – Nature. Now that huge amounts of information can be gathered and processed with ever-greater speed, graphic designers and illustrators are playing a crucial role in explaining what all the collected data really means and how we can make sense of it to improve our personal and professional lives. More than just a survey of finished work, Raw Data gets behind the final image to reveal how a stack of numbers can be transformed into a beautiful image rich with meaning and explanation. Among the international practices included are those who have been leading the way in the infographics revolution, along with a new generation of designers only just emerging from university.
Keywords: Grafische kunst; Graphic arts; Visuele communicatie